Pengaruh Brand Awareness Terhadap Keputusan Pasien Rawat Inap Umum Dalam Memilih RS St Madyang Kota Palopo - Nurfadhillah Rezky; A. Muhammad Multazam; A. Rezki Amelia (Window of Public Health Journal, 2025)
Brand awareness is a crucial element in healthcare marketing strategies that can significantly influence patients' decisions when choosing a hospital. This study aims to analyze the influence of brand awareness, encompassing aspects of recall, recognition, purchase, and consumption, on the decision-making process of general inpatients when choosing St. Madyang Hospital in Palopo City. This type of research employs a quantitative approach with a cross-sectional design. The sample in this study was 109 respondents, selected from the general inpatient population using a purposive sampling technique. Data were collected using a closed questionnaire and analyzed using the chi-square test and logistic regression analysis using the SPSS program. The results showed that the four brand awareness variables —namely, recall (p = 0.031), recognition (p = 0.040), purchase (p = 0.016), and consumption (p = 0.015) —had a significant influence on patients' decisions in choosing St. Madyang Hospital. This finding confirms that increasing brand awareness can be an effective strategy to attract patient interest in choosing healthcare services. This study concludes that all aspects of brand awareness, namely recall, recognition, purchase, and consumption, have a significant impact on patient decisions when choosing St. Madyang Hospital in Palopo City.